Ultrasound-Mediated Release of Hydrophilic and Lipophilic Agents From Echogenic Liposomes - Kopechek, Jonathan A. (2008)
OBJECTIVE: To achieve ultrasound-controlled drug delivery using echogenic liposomes (ELIPs), we assessed ultrasound-triggered release of hydrophilic and lipophilic agents in vitro using color Doppler ultrasound delivered with a clinical 6-MHz compact linear array transducer. METHODS: Calcein, a hydrophilic agent, and papaverine, a lipophilic agent, were each separately loaded into ELIPs. Calcein-loaded ELIP (C-ELIP) and papaverine-loaded ELIP (P-ELIP) solutions were circulated in a flow model and treated with 6-MHz color Doppler ultrasound or Triton X-100. Treatment with Triton X-100 was used to release the encapsulated calcein or papaverine content completely. The free calcein concentration in the solution was measured directly by spectrofluorimetry. The free papaverine in the solution was separated from liposome-bound papaverine by spin column filtration, and the resulting papaverine concentration was measured directly by absorbance spectrophotometry. Dynamic changes in echogenicity were assessed with low-output B-mode ultrasound (mechanical index, 0.04) as mean digital intensity. RESULTS: Color Doppler ultrasound caused calcein release from C-ELIPs compared with flow alone (P < .05) but did not induce papaverine release from P-ELIPs compared with flow alone (P > .05). Triton X-100 completely released liposome-associated calcein and papaverine. Initial echogenicity was higher for C-ELIPs than P-ELIPs. Color Doppler ultrasound and Triton X-100 treatments reduced echogenicity for both C-ELIPs and P-ELIPs (P < .05). CONCLUSIONS: The differential efficiency of ultrasound-mediated pharmaceutical release from ELIPs for water- and lipid-soluble compounds suggests that water-soluble drugs are better candidates for the design and development of ELIP-based ultrasound-controlled drug delivery systems.